Penerapan UB-Drainage (Underdrain Box Storage) Untuk Mereduksi Genangan Dan Meningkatkan Resapan Air Di Kampus UB - Priyantoro, Dwi; Juwono, Pitojo Tri; Suhardjono, Suhardjono; Ismoyo, M. Janu; Prasetyorini, Linda; Pranoto, Eko Suryo (Fakultas Teknik, Universitas Brawijaya, 2013)
Underdrain Box Storage is one of the conservation drainage (eco-drainage) that can be developed for a dense residential (urban villages). Surface runoff flows into the drainage channel and the bottom were the holes are arranged along the channel as a storage function, where the base of the shelter space in direct contact with the soil is the one concept offered.Construction Underdrain Box Storage consists of open channel, vertical drain hole, and box storage. The function of open channel is received runoff in the area. Vertical drain hole is continuing drain water runoff into the box storage. And the box storage as long storage is hold runoff to fill and absorb into the ground naturally. In addition, the application of underdrain box storage is reduced runoff in Jl.Yogyakarta (Veteran) until 83,34%. This system is capable to provide infiltration until 5% for on ce rainfall within 1hour.By considering the pattern of rainfall and its duration during the last 5 years in the UB campus, then every time the rainy season UB-Drainage system is able to contribute water infiltration by 45%.Keywords: underdrain box storage, run-off, reduced, infiltration